Four-to-six-year-olds’ developing metacognition and its association with learning outcomes - Chen, Shiyi; Green, Michaela; Hodge, Kathryn Nikki (Frontiers in Education, 2025)
IntroductionMetacognition is the ability to monitor and calibrate one’s cognitive processes. Prior studies have linked metacognition with learning outcomes; however, very limited research has examined young children’s metacognition. This study aims to investigate young children’s developing metacognition and its relation to their learning outcomes.MethodsA total of 74 typically developing children (Mage = 63.69 months) from a state in the Northwestern U.S. participated in this study. This cross-sectional study took place between 2023 and 2024. Metacognition was measured by a validated train track task, where children attempted to assemble two shapes using wooden train track pieces based on plans provided by the research assistants (RAs). This task was video recorded and coded independently by two trained RAs, using an established coding scheme. Children’s learning outcomes were measured by the Letter-Word Identification (language) and Applied Problems (mathematics) subsets in the Woodcock and Johnson IV-Achievement assessment.ResultsResults indicated that metacognition improved with age during early childhood, showing a larger increase between ages 5 and 6 compared to ages 4 and 5. Children’s metacognition scores did not differ significantly between boys and girls. Regression analysis showed that metacognition scores were significantly related to learning outcomes measured as the sum scores of language and mathematics assessments, controlling for children’s age.DiscussionOur study suggests that children who can effectively monitor and adjust their cognitive processes tend to have better academic outcomes, even at a very young age. Our finding indicates the importance of supporting children’s metacognitive skills, alongside traditional academic domains, to enhance overall learning outcomes.